Microempresa de lavado y secado de ropa en el cantón La Maná - Chaluisa Quishpe, Jorge Ernesto (2016)
This research project had as general objective conduct a feasibility study for the creation of a micro-washing and drying clothes in canton la Mana; the proposal was born as an alternative economic development of the microenterprise sector whose purpose was to provide better quality services to users, who expressed through surveys that there are deficiencies in the quality of care by micro dedicated to washing and drying of clothes. For market research aimed at the population of canton la Mana surveys were conducted using as an instrument questionnaires with multiple-choice questions that made it possible to obtain relevant data and information on the demand and preferences of service washing and drying clothes.